Transforming growth factor‐β1 inhibits interleukin‐1β‐induced expression of inflammatory genes and Cathepsin S activity in human vascular smooth muscle cells. (16th March 2021) - Dhaouadi, Nedra; Nehme, Ali; Faour, Wissam H.; Feugier, Patrick; Cerutti, Catherine; Kacem, Kamel; Eid, Ali H.; Li, Jacques‐Yuan; Zibara, Kazem
Abstract: Objective and design: This study investigated the opposite mechanisms by which IL‐1β and TGF‐β1 modulated the inflammatory and migratory phenotypes in cultured human intimal vascular smooth muscle cells vSMCs. Materials and treatment: Primary human vSMCs, obtained from twelve hypertensive patients who underwent carotid endarterectomy, were incubated for 24 hours with either 40 pM TGF‐β1, or 1 nmol/L IL‐1β, or their combination in presence or absence of anti‐TGF‐β neutralizing antibody. Methods: The expression levels of matrix metalloproteases and their inhibitors, and the elastolytic enzyme cathepsin S (CTSS) and its inhibitor cystatin C were evaluated with RT‐PCR. CTSS activity was measured by fluorometry. Results: TGF‐β1 reversed IL‐1β‐induced expression of iNOS, CXCL6, IL1R1, MMP12, and CTSS, while upregulated TIMP2 expression. Furthermore, anti‐TGF‐β neutralizing antibody abrogated TGF‐β effects. Combination with IL‐1β and TGF‐β1 induced the expression of IL1α, IL1β, IL1R1, and CTSS, but suppressed CST3 expression. CTSS expression in the combination treatment was higher than that of cells treated with anti‐TGF‐β antibodies alone. Moreover, IL‐1β‐induced CTSS enzymatic activity was reduced when human vSMCs were co‐treated with TGF‐β, whereas this reduction was abrogated by anti‐TGF‐β neutralizing antibody. Conclusion: TGF‐β1 abrogated IL‐1β‐induced expression of inflammatory genes and elastolytic activity in cultured human vSMCs. Thus, TGF‐β1 can play a crucial role in impairing IL‐1β‐induced vascular inflammation and damage involved in the etiology of cardiovascular diseases.